Temporal variability of climatic parameters and potential evapotranspiration - Patle GT; Khanna Manoj; Rai Anil; Sahoo RN; Sarangi A; Singh DK (Indian Journal of Agricultural Sciences, 2013)
A study was undertaken to evaluate the temporal variability in climatic parameters and potential evapotranspiration (PET) of reference crop. Time series data (1981-2011) of mean daily minimum and maximum temperature, mean daily temperature, relative humidity, wind speed and sunshine hours were analysed using Mann-Kendall test and Sens slope estimator to establish the trend. The CROPWAT model was used to estimate the PET. Minimum temperature, mean daily temperature, relative humidity and wind showed increasing trend, whereas sunshine hour and ET had decreasing trend. results revealed that mean daily minimum and mean daily temperature increased by 0.02dC/year and 0.01dC/year, respectively. Mean daily maximum temperature remained constant over the period as indicated by the Sens slope.Mean daily relative humidity and wind speed increased by 0.11;per year and 0.57;km/year during 1981-2011. Mean daily sunshine hours and reference evapotranspiration decreased by 0.06 hour/year and 0.01 mm/year, respectively during 1981-2011.
Keywords: Climate change; Evapotranspiration; Mann-Kendall test; Sens estimator; Trend analysis